Attitudes of Medical Imaging Technologists on Use of Gonad Shielding in General Radiography - MacKay, Molly; Hancy, Courtney; Crowe, Alan; D'Rozario, Ruth; Ng, Curtise (Australian Institute of Radiography, 2012)
Purpose: Gonad shielding is an important way to address the ‘as low as reasonably achievable’ (ALARA) requirement in radiography. However, its use relies on the attitudes of medical imaging technologists (MITs) to consistently adhere to professional conduct requirements relating to the application of gonad shielding. The purpose of this study was to investigate the attitudes of Western Australian (WA) MITs to the use of gonad shielding in general radiography and also to explore the variables influencing these attitudes. Methods: A questionnaire regarding MITs’ attitudes towards gonad shielding was developed based on relevant literature and distributed to MITs working in general radiography employed by public and private clinical centres in WA metropolitan and rural regions. Descriptive (percentage of frequency, mean and standard deviation) and inferential statistics (chi-square, t-test and analysis of variance) were used to analyse the responses of the multiple choice (MC) and 5 point scale questions from the returned questionnaires. Results: The questionnaire response rate was 44.6% (127/285). It was found that WA MITs perceived gonad shielding as important (mean: 3.8) and that adequate education had been provided (mean: 3.1). However, statistically significant attitude variations existed among MITs from different employment sectors (p < 0.01), equipment awareness (p < 0.05), genders (p < 0.005) and educational qualifications (p < 0.05).Conclusion: Overall WA MITs have positive and appropriate attitudes to the use of gonad shielding in general radiography. However, statistically significant attitude variations existed among MITs. Possible directions for improvement include the provision of gonad shielding protocol in each X-ray room in clinical departments and the enhancement of education and training of shielding application. This potentially will lead to improved consistency in the appropriate application of gonad protective shielding.